Voices : An Assessment of Perceived Risks Facing the Microfinance Sector in the Arab World - International Finance Corporation (International Finance Corporation, Washington, DC, 2016)
During the last decade, the microfinance sector in MENA has caromed from crisis to crisis. Some were caused by problems within the sector itself (Morocco crisis), while others were a product of the political instability that has gripped the region since the beginning of what was known then as the Arab Spring (early 2011). Within this context, this publication was developed as a joint collaboration between IFC’s MENA Microfinance Advisory Team and Sanabel, the Microfinance Network of Arab countries. It adopts the same methodology as the Global Microfinance Banana Skin and focuses on the main risks facing the industry in the Arab World today as seen by a broad range of stakeholders, from donors to microfinance institutions to regulators.